Sequential film marketing in China: The study of social platforms and their impacts - Yuntsai Chou; Wei Lin (Digital Business)
Because the Chinese movie market is regarded as the second-largest market worldwide, with digital advertising accounting for more than 50 % of a film's total expenditure, exploring the marketing effects of social platforms on box office performance in China is crucial for Hollywood studios. In this study, we defined a sequential process consisting of two marketing modes: broadcast before theatrical release and electronic word of mouth (eWOM) after release. The broadcast and eWOM modes were proxied by the volume and valence attributes of Maoyan and Douban, the two popular and professional platforms for video entertainment.Volume and valence on Maoyan and Douban were found to influence gross revenue, but volume on Maoyan has the highest predictive power. Marketing on Maoyan is primarily broadcast marketing, whereas that on Douban is only eWOM marketing. Additionally, Hollywood hits depend on sequential marketing to succeed. Distributors should allocate resources to increase the volume on Maoyan before a movie is released and volume and valence on Douban after its release.